Species names based on photographs: debate closed - Zhang, Zhi-Qiang (Zootaxa, 2017)
Discussions of current issues of broad interest in zoological taxonomy are encouraged in Zootaxa (Zhang 2007). One recent topic examines species names based on photographs without preserved specimens. This is not a new topic: as Ceríaco et al. (2016) correctly noted, this topic was previously discussed about a decade ago in Zootaxa (Dubois & Nemésio 2007; Donegan 2008), and was soon followed by a series of opinions and rebuttals when the critically endangered species Galápagos pink land iguana—Conolophus marthae Gentile & Snell, 2009—was named without a preserved holotype (Donegan 2009; Nemésio 2009a,b; Dubois 2009; Gentile & Snell 2009; Minelli 2009).